The Influence of Work Discipline, Work Motivation and Work Ability on Employee Performance at Pura District Office, Alor Regency - Gorang, Alvonso Fanisius (Jurnal Ilmiah Wahana Pendidikan, 2026)
The purpose of this study is to determine the effect of work discipline on employee performance, work motivation on performance, and ability on employee performance. Employee performance is a crucial issue in every organization. In this study, data were collected by distributing questionnaires to 20 respondents from the Pulau Pura District Office. A saturated sampling technique was used for data analysis, and multiple linear regression analysis was used using SPSS 26. A t-test was used to determine the partial effect and an F-test to determine the simultaneous effect on employee performance. The results of this study indicate that work discipline has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, and work ability has a positive and significant effect on employee performance.